Not only pigeons: avian olfactory navigation studied by satellite telemetry. Issue 3 (4th May 2021) - Bonadonna, Francesco; Gagliardo, Anna
Abstract : The olfactory navigation hypothesis proposed to explain homing pigeon navigation predicts that birds learn the association of wind directions and wind-borne odours at home, and once displaced, determine the home direction on the basis of local environmental odours at the release site. This hypothesis was proposed on the basis of two kinds of empirical observations: (i) pigeons develop navigational abilities only if exposed to winds at the home loft, (ii) anosmic pigeons displaced to unfamiliar sites are unable to home. Soon after the discovery of the role of olfaction in pigeon navigation about 50 years ago, olfactory navigation became a subject of hot scientific debate. Until the beginning of the GPS era, the large body of evidence in support of olfactory navigation in pigeons, swifts and starlings consisted mainly of vanishing bearings and homing performance data. The use of GPS, allowing the observation of the pigeons' behaviour en route provided further compelling evidence of the role of olfactory cues in pigeon navigation. The development of wildlife telemetry in the past two decades produced strong evidence about the use of olfactory cues, also in navigation of some species of wild birds. Wild birds artificially displaced both during migration, or during incubation showed impaired capacities to compensate displacements only if deprived of their sense of smell. Contrariwise, satellite telemetry failed to find any empirical validation for the existence of a navigational map based on magnetic cues in the tested species. In spite of the fact that the nature of the olfactory map in wild birds has not yet been elucidated, the development and miniaturisation of satellite technology will hopefully allow us in the near future to investigate in detail the features of the olfactory map found in some wild species, and to clarify the sensory basis of navigation in free-ranging small passerines.